Dielectric permittivity change detects the process of blood coagulation: Comparative study of dielectric coagulometry with rotational thromboelastometry. Issue 145 (September 2016) - Otaki, Yoichi; Ebana, Yusuke; Yoshikawa, Shunji; Isobe, Mitsuaki
Abstract: Background: Intravascular thrombus formation causes various cardiovascular diseases. To monitor coagulation is important for screening native status, prevention from bleeding and maintaining it within its therapeutic range. The prothrombin time and the activated partial thromboplastin time are widely used for assessment and recognized as the conventional methods. Prothrombin time methods employ enhancement of coagulation with thromboplastin. Since the laboratory data depend on the production lot and/or the manufacturer, the accurate methods are required for evaluation. Rotational thromboelastometry (ROTEM) is a method based on detection of the change in resistance to rotational movement during blood clotting, while dielectric blood coagulometry (DBCM) is a novel method for assessment of clotting by measuring the change of electrical permittivity. These methods are thus based on the technology for observation of different physical phenomena. The aim of this study was to compare parameters such as the clotting time obtained by ROTEM and DBCM to evaluate their clinical usefulness. Methods and results: ROTEM and DBCM parameters were measured in 128 patients. The ROTEM clotting time showed a significant positive correlation with the DBCM coagulation time (R = 0.707, p < 0.001). Comparison of the DBCM coagulation time between patients with and without anticoagulant therapy (including novel oral anticoagulants) revealed a significant difference (43.8 ± 11.9 min in the anticoagulant group vs 29.4 ± 8.3 min in the control group, p < 0.001). Evaluation of coagulation was equivalent with DBCM and ROTEM. Conclusions: The present study suggested that DBCM, a novel method for measuring blood clotting, could provide the detail assessment for the status of anticoagulant therapy. Highlights: Dielectric blood coagulometry (DBCM) is a new method for assessment of coagulation. DBCM showed a significant positive correlation with rotational thromboelastometry. DBCM could detect accurately the coagulation status. DBCM may offer a novel standardized assessment system for coagulation.